Validation of the DIGA-FAM Model: A Differentiated Game-Based Formative Assessment Using Wordwall - Vivi Indriyani; Ary Ramadhan; Anisa Nurjanah; Lira Hayu Afdetis Mana; Leli Lismay (Ta'dib, 2026)
Integrating differentiated instruction with game-based formative assessment remains underexplored in language education research, as most existing studies address these approaches in isolation rather than as a unified framework. Conventional formative assessment frequently fails to accommodate individual learner differences and lacks meaningful technology integration, limiting its effectiveness in diverse classroom contexts. To address this gap, this study develops and validates the DIGA-FAM Model (Differentiated Instruction and Game-Based Formative Assessment Model), a novel framework that systematically integrates gamification, formative assessment, and differentiated instruction using the Wordwall application. This study employed a development research design based on the Plomp (1997) model, focusing on the Prototyping Phase, which encompasses product elaboration and expert validation. Validation data were analyzed using descriptive quantitative and qualitative approaches. Expert validation results demonstrated high validity across three aspects: content (90%), language (91%), and graphics (82.5%), confirming that the model is theoretically sound and contextually appropriate for language learning. The DIGA-FAM Model contributes a replicable, differentiated formative assessment framework that bridges the gap between gamification and adaptive pedagogy, offering a structured alternative to conventional assessment practices in language education.